Bovine Ephemeral Fever (BEF) : Penyebab, Epidemiologi, Diagnosa, dan Terapi - Nururrozi, Alfarisa; Indarjulianto, Soedarmanto; Yanuartono, Yanuartono; Hary Purnamaningsih, Hary Purnamaningsih; Rahardjo, Slamet; Rusmihayati, Rusmihayati (Jurnal Sain Veteriner, 2020)
Bovine ephemeral fever (or 3-day sickness) is an acute febrile illness of cattle and water buffaloes caused by an Ephemerovirus of the family rhabdoviridae. The disease transmitted by arthropod vectors. It is common in tropical and subtropical regions. The main impact of BEF infection cause decreased productivity, decreased milk yield, body score and reproductive losses, and recovery can be prolonged in some animals. Clinical signs vary in individual animals, but the classic course begins with a fever, which is often biphasic to polyphasic. Mortality is typically low, however, significantly higher case fatality rates were reported in some recent outbreaks. This disease is widespread in various regions in Indonesia. In general, BEF does not cause large economic losses if medical assistance is provided sufficiently so that complications do not occur with other diseases. This paper aims to summarize the causes, epidemiology, diagnosis methods, and treatments that can be done to overcome BEF disease.